A Data-Driven Internal Controls Modeling Framework for Operational Risk Mitigation in Financial Services - Florence Ifeanyichukwu Olinmah,; Olayinka Abiola-Adams,; Bisayo Oluwatosin Otokiti,; Benjamin Monday Ojonugwa, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Operational risk poses a persistent threat to the stability and integrity of financial institutions, arising from failures in processes, systems, human actions, and external disruptions. In response to increasing regulatory scrutiny and complex operational environments, this paper proposes a robust data-driven internal controls modeling framework aimed at mitigating such risks. Departing from static, manual approaches, the framework introduces a layered architecture comprising data sources, analytics engines, control execution modules, and feedback loops. Each component functions interdependently to support real-time detection, response, and continuous improvement. The paper delineates how specific control typologies—including exception-based alerts and behavior-driven mechanisms—can be aligned with diverse operational risk categories. It further integrates these controls within enterprise risk management systems to ensure adaptive calibration and performance optimization. The framework offers both theoretical advancement in control systems research and practical utility for financial services practitioners seeking to modernize their risk management strategies. The paper concludes by identifying areas for future research in behavioral integration, advanced analytics, and cross-industry applications.
Keywords: Operational Risk; Internal Controls; Financial Services; Data-Driven Framework; Risk Mitigation; Predictive Analytics